350 Euston Road: Improving building performances and carbon footprint with innovative heating, ventilation and air conditioning solutions – A case study. (November 2017) - Draper, Phil
This case study paper describes the advantages of how heat pumps with heat recovery worked to contribute to improving energy performance and reducing the carbon footprint of buildings, with a short payback, thus showing it is a viable technology for energy cost reduction and for improving the environmental impact of buildings within the UK. All actions were taken based on performance for both the current and the future expected needs of the building and are measured against a baseline. The research and results confirm that heat pumps with heat recovery are a viable solution for London office buildings offering an integrated approach to building heating and cooling. The project resulted in a final reduction of 62% on the base building controlled utilities (total building less occupier power). The added benefits will be around the carbon benefits that the resultant 86% reduction in gas will bring due to the gradual de-carbonisation of the electric energy production in the UK. Practical application : This paper illustrates how to utilise an existing building's energy use data to determine how relatively simple technology can optimise the provision of simultaneous heating and cooling for comfort. It also details how modelled data can be used to allow the correct sizing of equipment to deliver both good internal comfort and low carbon emissions.